The role of intermittent PTH administration in conjunction with allogenic stem cell treatment to stimulate fracture healing. Issue 10 (1st October 2021) - Osagie-Clouard, Liza; Meeson, Richard; Sanghani-Kerai, Anita; Bostrom, Mathias; Briggs, Timothy; Blunn, Gorden
Abstract : Aims: A growing number of fractures progress to delayed or nonunion, causing significant morbidity and socioeconomic impact. Localized delivery of stem cells and subcutaneous parathyroid hormone (PTH) has been shown individually to accelerate bony regeneration. This study aimed to combine the therapies with the aim of upregulating fracture healing. Methods: A 1.5 mm femoral osteotomy (delayed union model) was created in 48 female juvenile Wistar rats, aged six to nine months, and stabilized using an external fixator. At day 0, animals were treated with intrafracture injections of 1 × 10 6 cells/kg bone marrow mesenchymal stem cells (MSCs) suspended in fibrin, daily subcutaneous injections of high (100 μg/kg) or low (25 μg/kg) dose PTH 1-34, or a combination of PTH and MSCs. A group with an empty gap served as a control. Five weeks post-surgery, the femur was excised for radiological, histomorphometric, micro-CT, and mechanical analysis. Results: Combination therapy treatment led to increased callus formation compared to controls. In the high-dose combination group there was significantly greater mineralized tissue volume and trabecular parameters compared to controls (p = 0.039). This translated to significantly improved stiffness (and ultimate load to failure (p = 0.049). The high-dose combination therapy group had the most significant improvement in mean modified Radiographic Union Score for Tibia fractures (RUST) compared to controls (13.8 (SD 1.3) vs 5.8 (SD 0.5)). All groups demonstrated significant increases in the radiological scores – RUST and Allen score – histologically compared to controls. Conclusion: We demonstrate the beneficial effect of localized MSC injections on fracture healing combined with low- or high-dose teriparatide, with efficacy dependent on PTH dose. Cite this article: Bone Joint Res  2021;10(10):659–667.